2011
DOI: 10.1177/1534765611430725
|View full text |Cite
|
Sign up to set email alerts
|

Markers of resilience in new police officers: Appraisal of potentially traumatizing events.

Abstract: This article presents data from a longitudinal study of adjustment to policing, specifically examining the role played by exposure to traumatic events prior to entry to the profession. This study aims to explore the impact of a prior traumatic experience on the appraisal of potentially traumatizing events experienced within the policing context. Seventy-eight police constables were followed from point of entry until the completion of 12 months of operational duties. The results suggest the experience of a trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…Distinct differences in training protocols between HA workers and other professions exposed to potentially traumatising events have been identified as a key factor underpinning differences in mental health outcomes between these populations (Burke and Shakespeare-Finch 2011). Review of the available HA literature indicates that predeployment training varies widely among organisations; it frequently involves international agencies training expatriate workers and is often very limited in nature (Connorton et al 2012;Ehrenreich and Elliott 2004;McCall and Salama 1999).…”
Section: Disparities In Training Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct differences in training protocols between HA workers and other professions exposed to potentially traumatising events have been identified as a key factor underpinning differences in mental health outcomes between these populations (Burke and Shakespeare-Finch 2011). Review of the available HA literature indicates that predeployment training varies widely among organisations; it frequently involves international agencies training expatriate workers and is often very limited in nature (Connorton et al 2012;Ehrenreich and Elliott 2004;McCall and Salama 1999).…”
Section: Disparities In Training Protocolsmentioning
confidence: 99%
“…These factors may predispose them to adverse mental health outcomes including depression, anxiety, occupational burnout and PTSD (Mollica et al 2004;Cardozo et al 2005;Dahlgren et al 2009). Conversely, training that specifically targets the risk and resilience profile of those who choose a profession is thought to produce workers who are more resilient to career challenges, thereby reducing the risk of adverse mental health outcomes (Burke and Shakespeare-Finch 2011). For example, it has been found that police officers often cope well with potentially traumatising events.…”
Section: Disparities In Training Protocolsmentioning
confidence: 99%
“…Research focusing on the development of pathology assumes that exposure to stress will likely result in a reduced level of psychological health (Burke and Shakespeare-Finch 2011). However, some individuals may experience positive outcomes and trajectories, which may include resilience (Bonanno 2005), compassion satisfaction (Stamm 2002), and posttraumatic growth (PTG; Calhoun and Tedeschi 2006).…”
Section: Positive Post-trauma Outcomesmentioning
confidence: 99%
“…Research examining emergency service worker well-being has tended to focus on those who occupy roles such as paramedics, police and fire-fighters. Such research has investigated the effects of a range of variables from personality factors (Shakespeare-Finch et al 2005), through to the impact of organisational and operational stressors (Brough 2005), and the impact of potentially traumatic events (PTEs) (e.g., Burke and Shakespeare-Finch 2011). Yet it is EMD's that are the vital first link that members of the community have with emergency medical responders.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic growth is considered an outcome of the process of coping with adversity and a desirable outcome that can help one deal with future trauma. For example, a study following new police recruits in Australia for 12 months after beginning service found that experiencing a trauma prior to joining the police force was associated with a tendency to adapt in a positive way to potentially traumatic events experienced on the job, based on their self-reported experience of post-traumatic growth (Burke and Shakespeare-Finch 2011).…”
Section: Not To Be Confused With Post-traumatic Growthmentioning
confidence: 99%